(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This article examines the role and importance of agriculture in the economy of the Republic of Uzbekistan and demonstrates the need to improve the competitiveness of fruit and vegetable products in future economic reforms and the need for implementing a network management system. The SWOT method also shows the prospects and ways to increase the competitiveness of fruits and vegetables in the global agrarian and food markets.